Growth and quality of Handroanthus serratifolius seedlings in soils incorporating amendments and inorganic residues - Ribeiro de Oliveira, Adriana; Boechat, Cácio Luiz; do Nascimento Amorim, Sarah Pricilla; Lopes de Souza, Manoel Emiliano; de Sousa Luz Duarte, Lizandra; França Silva, Helane (Revista Ceres, 2019)
Rock powder and boiler ash are residues with a high potential for the fertilization of substrates to produce forestry seedlings. They are the source of macro and micronutrients, besides having an effect on soil pH. Therefore, this study aimed to evaluate the effect of the isolated application of rock power, boiler ash, dolomitic limestone and calcium carbonate on the reaction of soils with a sandy and clayey texture in the Cerrado Piauiense and on the growth and quality of ipê-amarelo seedlings. For this purpose, the pH values of soil in water and CaCl2 solution and the following morphophysiological parameters as indicators of the quality of forest seedlings were analyzed: length of the aerial part (LAP), and root (RL), stem diameter (SD), number of leaves (NL), total chlorophyll (TC), fresh mass of the aerial part (FMAP), fresh mass of the root (FMR), dry mass of the aerial part (DMAP), of the root (DMR) and total (TRM), and the DMAP/DMR and LAP/SD ratios and Dickson quality index (DQI). It was found that the rock powder and boiler ash residues change the pH values in clayey and sandy soils, and promote the growth and quality of ipê-amarelo seedlings.